Impact of systematic cavity shave margins in breast‐conserving surgery at a large community hospital with a low baseline re‐excision rate. Issue 10 (19th October 2020) - Vetter, Christopher; Ashok, Aparna; Perez, Marla; Musaad, Salma; Rahimi, Gelareh; Gohil, Kavita; Higham, Anna
Abstract: Systematic cavity shave margins (CSM) can decrease rate of positive margins and re‐excision beyond that of selective CSM. The objective of this study was to determine whether systematic CSM decreased re‐excision rate in a population with a low baseline re‐excision rate. We conducted a retrospective chart review of patients who underwent breast‐conserving surgery (BCS) from November 2013 to November 2017. Primary end points were re‐excision rate and margin status. Secondary end points were total volume of tissue excised, operative time, and concordance of core needle biopsy (CNB) pathology with final surgical pathology. The re‐excision rates were 14.29% in the no shave margin group; 15.38% in the selective CSM; and 14.59% in the systematic CSM ( P  = .985). Odds of re‐excision with ductal carcinoma in situ (DCIS) was 5.04 times greater than with invasive cancer (INV) and 1.94 times higher than with INV and DCIS. There was no significant difference in positive margins between groups ( P  = .362). Mean specimen volume was lowest in the systematic CSM group (64.6 cm 3 ), compared to no CSM and selective CSM (94.6 cm 3 and 91.8 cm 3, respectively). With inclusion of shave margin volumes, total volume removed was not significantly different between no shave margin group (94.6 cm 3 ) and systematic CSM (89.7 cm 3 ) ( P  = .949). For patients with invasive ductal carcinoma (IDC) alone on their initial biopsy pathology, 69% were discovered to also have DCIS upon final pathology. Re‐excision rate and specimen volume between all groups were not statistically different. There was a higher re‐excision rate when DCIS was present, especially when not identified on CNB. As systematic CSM is most impactful when DCIS is involved, it is important to establish its presence for proper surgical planning.